The violence of victory: moral collapse in Euripides’ The Trojan Women - Regis, Eunice (My University, 2026)
This paper offers an in-depth analysis of Euripides' The Trojan Women, examining its exploration of the emotional, psychological, and social ramifications of war. The study highlights the fates of key characters—Hecuba, Cassandra, Andromache, and Helen—showcasing their struggles and resilience in the war's aftermath. By drawing parallels between the play and contemporary events such as the Peloponnesian War and the Melian Dialogue, the author contends that Euripides critiques the inherent brutality of war and the moral degradation of the victors. Through this examination, themes of grief, loss, and existential despair are explored, underscoring the timeless relevance of The Trojan Women and its profound insights into the human condition during periods of crisis.
Keywords: Euripides; The Trojan Women; brutality of war; moral degradation; human condition